King's Parkinson's Disease Pain Questionnaire: reliability and convergent construct validity - Ana Carolina Sartori; Fânia Cristina dos Santos; Juliana de Lima Lopes; Vinicius Batista Santos; Meiry Fernanda Pinto Okuno (Associação Brasileira de Enfermagem, 2023)
ABSTRACT Objectives: to assess the evidence of reliability and convergent construct validity of the King's Parkinson's Disease Pain Questionnaire. Methods: psychometric study of 75 older adults with Parkinson's disease. The instrument was applied by two researchers separately and reapplied by one researcher 15 days later. In terms of reliability, internal consistency was assessed using the Cronbach's alpha test and stability using the intraclass correlation coefficient. Scores of the King's Parkinson's Disease Pain Questionnaire were compared to those of the Geriatric Pain Measure in the assessment of construct validity. Results: the mean Cronbach's alpha obtained between the three assessments was above 0.60, the intraclass correlation between the three assessments was above 0.90, and there was a weak but significant correlation between the two applied scales. Conclusions: the instrument showed adequate evidence of convergent construct validity and reliability, and can be used in clinical practice.